A revision of the type specimens of Tertiary molluscs from Chile and Argentina described by d`Orbigny (1842), Sowerby (1846), and Hupé (1854) - Griffin, Miguel (2008)
Fil: Griffin, Miguel. Facultad de Ciencias Exactas y Naturales; Universidad Nacional de La Pampa